Research analysis of saponite clay properties - Рудь, Віктор Дмитрович; Самчук, Людмила Михайлівна; Савюк, Ігор Віталійович; Повстяна, Юлія Славомирівна (Technology audit and production reserves, 2015)
This paper analyzes the work aimed to research of natural material - saponite. The properties of this material are analyzed. An X-ray and metallographic analysis of three layers of saponite clay is conducted. In order to test the chemical composition, given by above authors, preliminary X-ray analysis of three saponite layers of Tashkovsky field is conducted. Researches were conducted to determine and compare the structure of each of the saponite clay layers. It is visible on the images that saponite has a large number of capillaries and pores of micron size. By the method of metallographic analysis it is established that saponite has an amorphous structure. It is determined that the proposed material has good sorption properties, which further leads to its use for filtering the drinking and waste water. The results of this research serve as an impetus for the research of saponite clays to expand their applications.